Παραμετρική μελέτη θέρμανσης ζεστού νερού χρήσης με ηλιακή ενέργεια με τη χρήση του προγράμματος F-Chart - Χρίστου, Γιώργος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The current BSc thesis entitled "Parametric study heating hot water by solar energy using the program F-Chart» was prepared by George Christou, senior student of the Department of Mechanical Engineering and Materials Science and Engineering from the Cyprus University of Technology, under the supervision of the Associate Professor, Mr Ioannis Michaelides, and was completed in May of 2013. The subject of this thesis is to compare the performance and economic competitiveness of solar water heating systems, which make use of solar collectos that vary in construction, operation, quality, thermal efficiency and cost related to their initial cost and installation. This comparison takes place between 24 different models of solar panels, collected from 11 different Cypriots and one Chinese manufacturers (2 solar panels from any manufacturer) and aims to the selection of the optimal economic number of solar panels which are going to be installed on a solar thermal system that satisfies the demand for domestic hot water (DHW) of a hotel complex which has the capacity to hold up to 300 people. After a review of existing knowledge and experience, regarding the demand of domestic hot water and the solar thermal systems at hotel complexes, information about the various types of solar collectors, their thermal efficiency, the cost of purchasing and installation are collected, in order to start the analysis of the system using the specialized software program “F-Chart”. Analysis is conducted parametrically by altering important aspects of solar panels including economic parameters until we reach the optimum result. After the simulation process, we obtain results concerning the annual thermal efficiency of each type of solar collector, the optimal economic number of solar panels that will make up the solar thermal system in the hotel complex as well as the financial analysis of the system. According to these results, it is observed that during the winter period, the demand for DHW is increased, up to a maximum value, due to low temperatures and the minimum incident solar radiation on the collector surface. As a result, the demand for power from an auxiliary energy source, such as oil, increases having as a result a higher cost. On the other hand, during the summer period, because of the high temperatures and the maximum incident solar radiation on the collector surface, the demand for DHW and auxiliary energy source are reduced. Furthermore, it is observed that, regardless of the cost per m2 of a solar collector’s area and the type of solar collector and in case that the number of solar panels in the whole system exceeds the optimal economic number of solar panels in the system for each type of collector, there will be no improvement in heating domestic water, but the total cost of the installation will increase. Finally, we conclude that the profitable and more economic solution for an owner, it is neither the choice of a collector with very high efficiency and high cost nor the choice of a collector with very low efficiency and lower costs. The best solution is buying a collector situated at an intermediate cost and average efficiency, not too expensive nor the cheapest, since no significant difference in performance and efficiency between an expensive and an intermediate cost type of solar collector, and comparing the cheapest collector and a middle class one, the middle class requires a reduced number of panels, which means less cost and therefore economical solution. Also, comparing the Chinese and Cypriot solar panels, choosing a Cypriot solar collector is the most advantageous option.
Keywords: Performance Of Solar Water Heating Systems; Solar Collectos; Απόδοση Ηλιακού Συστήματος Παραγωγής Ζεστού Νερού Χρήσης; Ηλιακοί Συλλέκτες